THE RELATIONSHIP BETWEEN SELF-CONCEPT AND LEARNING DISCIPLINE WITH MATHEMATICS LEARNING OF STUDENT CLASS VII - Tia Gustiani Barokah; Edi Prajitno (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
Low student mathematics learning outcomes are associated with several factors. The relationship between self-concept and discipline of learning are some factors that may be related to learning outcomes. This research aims to know about the positive relationships and the significant between self-concept and discipline of learning with mathematics outcomes of students class VII even semester Islamic State Junior High School (MTs Negeri) 4 Bantul period 2017/2018. The Population in this research is the student of Class VII, even semester Mts Negeri Bantul, period 2017/2018, consisting of 8 classes, which totaling 228 students. The samples are taken randomly from class VII D as class sample research using a random sampling technique. Data collection technique using questioner method to get the self-concept and discipline of learning data and a test method to get mathematics outcomes data. The Instrument research test is a validity test, difference test, and reliability test. Prerequisite analysis tests are the normality test, linearity test, and Independency test. Data analysis using product moment analysis and multiple linear regression analysis. The research finding shows positive relation and significance between self-concept and discipline of learning with mathematics learning outcomes student’s class VII even semester MTs Negeri 4 Bantul period 2017/2018. This is showing by fcount>ftable, that is With RC = , RC = While EC = and EC =